Middle Managers' Upward Roles in the Public Sector. (May 2017) - Chen, Chung-An; Berman, Evan M.; Wang, Chun-Yuan
Whereas previous public administration studies have focused on middle managers' roles in implementation, this study contributes to the literature by emphasizing middle managers' other roles, specifically, upward roles that concern (a) championing alternatives and (b) synthesizing information. We examine whether middle managers are more involved in synthesizing information than championing alternatives and test multiple levers that increase these roles at the individual, organization, and interorganizational levels. This study finds that job security, connections with stakeholders, and autonomous motivation are among the most important predictors. This study calls for taking a broader perspective on middle managers' contributions to public organizations.